PERSAMAAN DAN PERBEDAAN ANTARA SANKSI HUKUM ISLAM DAN HUKUM POSITIF TENTANG SANKSI HUKUM TERHADAP PELAKU ABORTUS - adnan, Latifah (Media Akademika, 2016)
Both positive law and Islamic law considers absortion as a despicableÂ  act, becauseÂ  it is opposen to moral and ethical. And the perpetrators of such actsÂ  are entitled to legal sanctions as aÂ  result if indecency that they did. This study discusses the legalÂ  punishment of abortus provocatus according to the concept of Imam Maliki and Imam SyafiâI. In the opinion of Imam MalikiÂ  and Imam Syafiâi, those who perform abortion intentionally (abortus provocatus) subject to two legal sanctions, namely diyat law sanctions (fines) and kifarat law sanctions.